Curcumin Improved The Sperm Motility of Oligo-Asthenoteratozoospermia Patients during Cryopreservation by Regulating Mitochondrial Apoptotic Pathway Genes and Improving The Antioxidant Capacity of Cells - Farnoush Naseri; Seyed Abdolhamid Angaji; Elham Siasy; Maryam Peyvandi (International Journal of Fertility and Sterility)
Background: Oligo-asthenoteratozoospermia (OAT) is one of the causes of male subinfertility, and one of the treatment solutions is sperm cryopreservation. However, during the freezing-thawing process, sperm parameters decrease. It is important to find compounds that can prevent the reduction of sperm parameters. The aim of this study is to reduce male infertility through sperm preservation.Materials and Methods: In this experimental study, thirty OAT patients meeting the inclusion criteria were selected for the current research. Initially, the patients were studied by karyotyping, and all of them were normal 46 XY. After that, sperm samples were taken from them. Sperm parameters such as viability, concentration, motility and percentage of abnormal morphology were determined before cryopreservation. Then, the samples were divided into four aliquots and placed in cryopreservation medium supplemented with different concentrations of curcumin (0, 15, 20, and 25 μM). These samples were placed in a nitrogen tank. After 7 days, the samples were thawed, and sperm parameters were measured. In the next step, the content of malondialdehyde (MDA) and the activities of antioxidant enzymes superoxide dismutase (SOD) and glutathione peroxidase (GPx) were measured by kits. Finally, after RNA extraction and cDNA synthesis, the expression levels of the BAD, B-cell lymphoma-extra large (BCL-XL) and microRNA-21 (MIR-21) genes were investigated using reverse transcription polymerase chain reaction (RT-PCR).Results: Curcumin (20 μM) conserved OAT sperm motility after the freezing-thawing process. Additionally, this concentration of curcumin decreased MDA and improved SOD and GPx activities in cryopreserved sperm. The results of gene expression analysis showed downregulation of BAD and overexpression of both BCL-XL and MIR-21 in 20 μM curcumin-treated sperm after the freezing-thawing process.Conclusion: It can be concluded that adding appropriate antioxidants to the sperm freezing medium can greatly reduce the destructive effects of oxidative stress and improve sperm motility.